The Effect of Oil Spills on Infant Mortality: Evidence from Nigeria - Anna Bruederle; Roland Hodler (Center for Economic Studies and ifo Institute (CESifo), 2017)
Oil spills can lead to irreversible environmental degradation and pose hazards to human health. We are the first to study the causal effects of onshore oil spills on neonatal and infant mortality rates. We use spatial data from the Nigerian Oil Spill Monitor and the Demographic and Health Surveys, and rely on the comparison of siblings conceived before and after nearby oil spills. We find that nearby oil spills double the neonatal mortality rate. These effects are fairly uniform across locations and socio-economic backgrounds. We also provide some evidence for negative health effects of nearby oil spills on surviving children.
Keywords: I10; I18; J13; Q53; 330; oil spills; Nigeria; infant mortality; child health